Analysis of the Meaning of Referential and Non-Referential Lyrics of the Malay Song Sambas on the Album of Terigas 2 - Heru Susanto; Susan Neni Triani; Eti Sunarsih; Nurwati Nurwati; Slamat Fitriyadi; Kamaruddin Kamaruddin; Lili Yanti; Rahmatika Dewi (STKIP Singkawang, 2022)
This research was motivated by the referential meaning and non-referential meaning contained in the album of Terigas 2. This study aims to (1) describe how referential meaning refers to objects in the lyrics of the Malay song Sambas on the album of Terigas 2, (2) describe how the referential meaning refers to events in the lyrics of the Malay song Sambas on the album of Terigas. 2, (3) describe how the non-referential meaning in the form of prepositions in the lyrics of the Malay song Sambas on the album of Terigas 2, and (4) describe how the non-referential meaning in the form of conjunctions in the lyrics of the Malay song Sambas on the album of Terigas 2. This study used a descriptive method in the form of qualitative research. The source of data in this study came from the album Terigas 2 and the data in this study was a series of words in the album Terigas 2 which contain referential and non-referential meanings. The data collection technique used was a documentary study technique and the tools used were the researchers themselves as key instruments and data recording cards. There were five data analysis techniques used in this study which included reading/understanding data, classifying data, selecting data, analyzing data, and concluding data. Based on the results of the study obtained 85 data, namely the referential meaning in the form of objects totalling 51 data, referential meaning in the form of events totalling 19 data, non-referential meaning in the form of prepositions totalling 3 data, and non-referential meaning in the form of conjunctions totalling 12 data.